Effect of Transaction Costs on Profit and the Capital Formation of Soybean Farming in Lamongan Regency, East Java - Sultan, Hardiyanti; Rachmina, Dwi; Fariyanti, Anna (AGRARIS: Journal of Agribusiness and Rural Development Research, 2021)
Transaction costs was one of imperfect market characteristic. The transaction costs of soybean farming affected profit level, and profit was one factor of capital formation. This research aimed to analyze the structure and the effect of transaction costs on the profitability and the capital formation of soybean farming. This study applied transaction cost analysis and simultaneous equation as the methods. The respondents were determined using simple random sampling by taking the proportion of 25% for the three selected districts, resulting in 120 respondents. The data were the transaction costs in 2014/2015 and household data from 2012 to 2014, comprising the assets of land, vehicles, farm equipment, crop, and livestock. The results revealed that the transaction costs were IDR 144,120.86. The negotiation costs became the highest cost component (60.30%), followed by information costs (14.07%), coordination costs (12.22%), implementation costs (8.03%), monitoring costs (4.23%) and risk costs (1.15%). Transaction costs had a significant effect on the profitability of soybean farming. The highest percentage of capital formation on soybean farming was for farmland, reaching 40.43%. Other capitals included vehicles (24.59%), plants (19.31%), building (7.37%), and supporting tools (3.09%). Transaction costs did not significantly effect on farming capital formation. As a recommendation, collective action was required, farmers should be active on farmers groups to reduce transaction costs.